Cataloguing in an automated library:policy options for libraries in developing countries (2011)
The tremendous growth of information and its utilization has led to the emergence and use Information and Communication Technology (ICT) in libraries. The use of ICT is obvious in the information handling process. The introduction of automation in cataloguing has opened up a new era of information processing in libraries. While many libraries in developed countries have embrased automated cataloguing, only few libraries embraced this technology in developing countries. The art of cataloguing is in a state of constant dynamic change due to advancement in ICT. The capabilities of automation are causing changes in the tools used by cataloguers. Catalogues are being computerised all over the world to facilitate better access points and multidimensional searches in the library holdings. As result of these, this article gives an exploration of cataloguing in the library before the advent of automation as well as cataloguing in an automated age. It also attempts to discuss cataloguers' roles in an automated library. There are many policy implications which should be given due considerations as the library materials are being processed electronically. The paper therefore suggests that the library management needs to be pro-active rather than reactive, ensure relevant training and re-training of cataloguers on the use of these modern tools in cataloguing by sending cataloguing staff to attend conferences, seminars and workshops in order to update their knowledge and maintain awareness of current trends in cataloguing, maintenance of the infrastructure, patrons education, among others.